Effects of the multidrug resistance modulator HZ08 on the apoptosis pathway in human chronic leukaemia cell line K562/A02 - Cen, Juan; Zhu, Yi-Lin; Yang, Yu; Zhu, Jun-Rong; Fang, Wei-Rong; Huang, Wen-Long; Li, Yun-Man; Tao, Yi-Fu (Arzneimittelforschung, 2011)
Cancer fails to respond to chemotherapy by acquiring multidrug resistance in over 90% of patients. A previous study revealed that multidrug resistance modulator HZ08 had great multidrug resistance reversal effect in vitro and in vivo. It could enhance adriamycin (doxorubicin) induced intrinsic apoptosis pathway and rectify cell cycle and some apoptosis related proteins in human breast resistant cancer MCF-7/ADM cells. This study detected Rh l23 accumulation to assess the effect of HZ08 on P-glycoprotein function in human chronic leukaemia cell line K562/A02. Moreover, mitochondria membrane potential, cytochrome c release and caspase-3 activity were analyzed for HZ08 treatment with or without vincristine. Since pretreatment with HZ08 could also reverse the multidrug resistance to vincristine in K562/A02 cells, the individual influence of HZ08 was further detected on apoptotic regulator like Bcl-2, Bax, p53, cell cycle checkpoints and proliferation regulatory factors like survivin, hTERT, c-Myc, c-Fos, c-Jun. Finally, it revealed that HZ08 increased vincristine induced activation in intrinsic apoptosis pathway by inhibition of P-gp mediated efflux. In addition, the outstanding reversal effect of HZ08 should also attribute to its individual effect on apoptosis and proliferation related regulatory factors. It renders HZ08 possibility of application in pretreatment to reverse multidrug resistance while avoiding unexpected drug interactions and accumulative toxicity.
Keywords: Apoptosis; Cancer; Human telomerase reverse transcriptase; HZ08; K562/A02 cells; Multidrug resistance